Pengembangan Praktek Mengajar Pendidikan Kewirausahaan pada Masa Covid-19 Menggunakan Aplikasi Google Classroom - Nazaruddin Ali Basyah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The purpose of this activity is to introduce new tools that will help educators to be more effective in learning. In a review of the theory, framework and model of eLearning, Mayes and de Freitas especially that it is important to explain about the assumptions that build e-learning design, they claim that in fact there is no specific model for e-learning, only an improvement of the existing learning model that uses e-learning. technology to achieve better learning outcomes. Google Classroom is one of the free services by Google package within Gsuite for Education. This training was carried out for teachers in the fields of economics and entrepreneurship throughout Aceh online via Zoom meetings. It promotes paperless instruction to streamline tasks, can improve collaboration and communication to make teaching more productive and meaningful. Google Classroom can be easily deployed at the URL classroom.google.com, educators can set up classes in minutes and create content for students. He is also free to school, best in class security is also included at no cost to plan holders. The platform also integrates with other Google tools to help educators provide feedback and track progress to improve performance, it also has a mobile app for easy access anytime and anywhere.